Efek Kualitas Pelayanan Terhadap Citra Gojek Pada Mahasiswa Universitas Islam Riau - Sujatmiko, Ary; Setiawan, Harry (Riauan Consulting and Communication, 2022)
This study aims to determine the effect of service quality on the image of Go-Jek on FIKOM students, Islamic University of Riau. This type of research is associative with a total population of 1,246 people. The sampling used was simple random sampling, which is a random sampling technique of 93 people. The statistical measurement of the sample in this study was conducted to determine the significance of each difference in the mean value of each variable. From the results of the t test, the tcount value of 7.475 is greater than ttable of 1.985 so the quality of service has a significant effect on Go-Jek's image, while the R2 test with a correlation coefficient (R) of 0.617 means that there is a strong relationship between service quality and Go-Jek image. Coefficient of determination (R2) is 0.380, which means that service quality has an influence of 38% on Go-Jek's image, the remaining 62% is influenced by factors not examined.